2020
DOI: 10.1136/vr.105631
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes are important factors in farmers’ choice of lamb tail docking length

Abstract: BackgroundTail docking is common practice in the sheep industry to prevent soiling of the breech and flystrike. To ensure optimal healing after tail docking and reduce the risk of arthritis, perineal cancers and prolapses, it is recommended to dock tails equivalent to the length of the vulva. However, recent studies have found that some tails are docked too short (24–86 per cent).MethodsTo address this issue, this study aimed to identify key drivers behind tail docking length decisions. Two focus groups, phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…They found that many farmers docked the tails of their sheep too short, either because they were not aware of the recommended length or because they were docking at a length that suited shearers. 9 Woodruf and colleagues suggest that educating farmers on the recommended length is imperative to improve sheep welfare. Where farmers get their advice from, who they trust, how they learn and, thus, how best to intervene is an evolving ield of investigation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…They found that many farmers docked the tails of their sheep too short, either because they were not aware of the recommended length or because they were docking at a length that suited shearers. 9 Woodruf and colleagues suggest that educating farmers on the recommended length is imperative to improve sheep welfare. Where farmers get their advice from, who they trust, how they learn and, thus, how best to intervene is an evolving ield of investigation.…”
mentioning
confidence: 99%
“…Since animal welfare is as much about people as it is about animals, 7 it is surprising that there have, with some exceptions, 8 been few insights into the reasons why farmers choose to dock the tails of sheep shorter than the recommended length. In a study summarised on p 319 of this issue of Vet Record , 9 Woodruff and colleagues sought to understand the beliefs and attitudes driving farmers’ tail docking practices as a prerequisite to designing interventions to change behaviours. They found that many farmers docked the tails of their sheep too short, either because they were not aware of the recommended length or because they were docking at a length that suited shearers 9 …”
mentioning
confidence: 99%
See 3 more Smart Citations